Wavelength-adjustable long afterglow composite material as well as preparation method and application thereof

By preparing an inorganic oxide coating on the surface of a mixture of long afterglow fluorescent material and perovskite quantum dot material, the problems of intimate bonding and poor stability in the prior art are solved, and the stability and fluorescence of the composite material are improved Lifespan meets the needs of multi-color applications.

CN119220243APending Publication Date: 2024-12-31WUXI UTMOST LIGHT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310782444.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing quantum dot-rare earth long afterglow composite luminescent materials are not tightly bonded, have poor stability, and have short fluorescence life, making it difficult to meet the needs of multicolor applications.

Method used

A mixture of long afterglow fluorescent material and perovskite quantum dot material is used, and an inorganic oxide coating is prepared on the surface of the mixture, using ethyl orthosilicate, tetramethyl orthosilicate, and 3-aminopropyl triethylene Materials such as oxysilane, tetrabutyl titanate, aluminum isopropoxide, etc. are coated to improve the stability and energy transfer efficiency of the material through hydrolysis and sintering steps.

Benefits of technology

The close combination of long afterglow fluorescent materials and perovskite quantum dot materials has been achieved, which improves the stability and fluorescence lifetime of composite materials, and enhances the application potential of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220243A_ABST
    Figure CN119220243A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoluminescent materials, and particularly relates to a wavelength-adjustable long afterglow composite material as well as a preparation method and application thereof. According to the invention, a long-afterglow fluorescent material is used as an energy storage unit and is combined with a perovskite quantum dot composite material with an adjustable emission peak position, long-wave perovskite quantum dots are excited by short waves of the long-afterglow fluorescent material, and a mixture with long afterglow and adjustable luminescence characteristics is obtained. Preparing a coating layer on the surface of the mixture by adopting tetraethoxysilane, tetramethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrabutyl titanate, aluminum isopropoxide, aluminum n-butoxide and the like, and after the coating material is hydrolyzed, coating the surface of the mixture with inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide and the like; on one hand, the coating material is used as an adhesive, so that the two materials are combined more tightly; on the other hand, as a coating body, the stability of the two and the fluorescence lifetime of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoluminescent materials, and in particular relates to a wavelength-adjustable long afterglow composite material and a preparation method and application thereof. Background Art

[0002] Long afterglow luminescent materials are functional materials that can store energy irradiated by external light under natural light or other artificial light sources, and gradually release the stored energy in the form of light after the excitation stops. At present, they are mainly used in application fields such as indicator lighting, architectural decoration, biological imaging, and information storage. According to the luminescent color, long afterglow luminescent materials can be divided into different types (red, yellow, green, blue, etc.); among them, a large number of long afterglow materials in practical applications are only green rare earth aluminates, which is difficult to meet the needs of designing multi-color application products through long afterglow luminescent materials. In addition, although rare earth aluminates have excellent afterglow performance, due to the limited penetration ability of green light, their application in special environments (fog, rainy days) is more restricted. In contrast, red light or yellow light has better penetration characteristics. The safety signs designed with red long afterglow luminescent materials have a strong warning effect. Therefore, the research and development of multi-color long afterglow luminescent materials is of great research significance and practical application value.

[0003] For example, existing patent documents disclose a quantum dot-rare earth long afterglow composite luminescent material and a preparation method thereof. The composite material is composed of a rare earth long afterglow luminescent material and quantum dots. The preparation is simple, and the rare earth long afterglow luminescent material and quantum dots only need to be spin-coated into a film or directly mixed. By regulating the type and ratio of the rare earth long afterglow luminescent material and the quantum dots, the composite material can achieve efficient long afterglow luminescence in the entire visible spectrum. However, the quantum dot-rare earth long afterglow composite luminescent material prepared by this method has loose bonding between materials, poor stability, and short fluorescence lifetime. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects of the quantum dot-rare earth long afterglow composite luminescent material in the prior art, thereby providing a wavelength-adjustable long afterglow composite material and its preparation method and application.

[0005] To this end, the present invention provides the following technical solutions:

[0006] The present invention provides a wavelength-adjustable long-afterglow composite material, comprising a mixture of a long-afterglow fluorescent material and a perovskite quantum dot material, and an inorganic oxide coating layer coated on the surface of the mixture;

[0007] Wherein, the inorganic oxide coating layer is prepared from at least one of ethyl orthosilicate, tetramethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrabutyl titanate, aluminum isopropoxide, and aluminum n-butoxide.

[0008] Optionally, the mass ratio of the long afterglow fluorescent material to the perovskite quantum dot material is 100:1-1:100.

[0009] In some embodiments, the mass ratio of the long afterglow fluorescent material to the perovskite quantum dot material is 100:1, 90:1, 80:1, 70:1, 60:1, 50:1, 40:1, 30:1, 20:1, 10:1, 5:1, 3:1, 1:1, 1:2, 1:5, 1:10, 1:20, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100, etc.

[0010] Optionally, the afterglow wavelength of the long afterglow fluorescent material can excite the perovskite quantum dot material; normally it can be shorter than the emission wavelength of the perovskite quantum dots.

[0011] Optionally, the afterglow wavelength of the long afterglow fluorescent material is less than 10 nm of the emission wavelength of the perovskite quantum dot material.

[0012] Optionally, the long afterglow fluorescent material includes at least one of rare earth doped aluminate, rare earth doped silicate and sulfide fluorescent materials.

[0013] Optionally, the perovskite quantum dot material includes at least one of perovskite quantum dot glass, perovskite quantum dot@molecular sieve composite material, perovskite quantum dot@mesoporous material composite material, perovskite quantum dot@mesoporous material composite material, perovskite quantum dot@multi-level porous material composite material, and perovskite quantum dot core-shell coating material;

[0014] And / or, the perovskite quantum dot material includes at least one of CsPbX3 and ion-doped perovskite quantum dots;

[0015] Optionally, the composition of the ion-doped perovskite quantum dots is CsPb a M 1-a X3, M is selected from at least one of Sr, Ca, Ba, Mn and rare earth ions.

[0016] The present invention also provides a method for preparing the above-mentioned wavelength-adjustable long afterglow composite material, which is characterized by comprising the following steps:

[0017] S1, mixing a long afterglow fluorescent material with a perovskite quantum dot material to obtain a mixed powder, and dispersing the mixed powder in an organic solvent;

[0018] S2, adding the coating material dropwise, hydrolyzing, drying, grinding, and sintering to obtain the wavelength-adjustable long afterglow composite material.

[0019] Optionally, in step S2, the sintering temperature is 200-700°C, and the sintering time is 30min-15h;

[0020] Optionally, the sintering step includes maintaining the temperature at 380-420° C. for 2-6 hours, and then increasing the temperature to 450-540° C. for 3-10 hours;

[0021] And / or, the sintering is performed under a protective atmosphere.

[0022] Optionally, the ratio of the amount of coating material to the mixed powder is 0.2-20 mL / g.

[0023] Optionally, in step S1, the ratio of the amount of the organic solvent to the mixed powder is 1-200 mL / g;

[0024] And / or, the organic solvent comprises at least one of ethanol, propanol, n-hexane and cyclohexane;

[0025] And / or, the particle size of the mixed powder is controlled to be 200-2000 mesh.

[0026] The present invention also provides an application of the above-mentioned wavelength-adjustable long afterglow composite material or the wavelength-adjustable long afterglow composite material prepared by the above-mentioned preparation method in the fields of indicator lighting, architectural decoration, biological imaging, information storage, biological detection, anti-counterfeiting labeling, photoelectric detectors or solar spectrum conversion.

[0027] The present invention has no special requirements on the source of each raw material, which can be obtained through commercial channels or prepared by itself. Typically, but not limitedly, the preparation of the perovskite quantum dot glass includes the following steps:

[0028] The glass matrix, cesium source, lead source and halogen source are mixed and stirred evenly, fully ground and then sintered and melted at high temperature (600-1400°C) to disperse the elements evenly in the glass melt and cast on a brass plate. The obtained glass blocks are crushed and ground and collected for later use.

[0029] Optionally, the glass matrix is ​​not limited to borosilicate glass, but also includes phosphate glass, germanate glass, antimonate glass, etc.

[0030] The perovskite quantum dot materials used in the present invention are not limited to perovskite quantum dot glass, but also include perovskite quantum dot@molecular sieve composite materials, perovskite quantum dot@mesoporous / mesoporous / multi-level porous composite materials, perovskite quantum dot core-shell coating materials and other perovskite quantum dot coating materials. For example, other coating materials can be photothermal, photoelectric, photocatalytic conversion materials, etc.

[0031] The perovskite quantum dots in the perovskite quantum dot material used in the present invention are not limited to CsPbX3, but also include various ion-doped quantum dots such as CsPb a M 1-a X3, M can be divalent or trivalent metal ions such as Sr, Ca, Ba, Mn, Ln (Ln = rare earth ions such as La, Eu, Dy, Tb, Yb, etc.).

[0032] The technical solution of the present invention has the following advantages:

[0033] The present invention provides a wavelength-adjustable long-afterglow composite material, comprising a mixture of a long-afterglow fluorescent material and a perovskite quantum dot material, and an inorganic oxide coating layer coated on the surface of the mixture; wherein the inorganic oxide coating layer is prepared from at least one of ethyl orthosilicate, tetramethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrabutyl titanate, aluminum isopropoxide, and aluminum n-butoxide. The present invention innovatively proposes a composite material that uses a long afterglow fluorescent material as an energy storage unit and a perovskite quantum dot composite material with adjustable emission peaks. The long afterglow fluorescent material is used to excite long-wave perovskite quantum dots with short wavelengths to obtain a mixture that has both long afterglow and adjustable luminescence properties. Then, ethyl orthosilicate, tetramethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrabutyl titanate, aluminum isopropoxide, aluminum n-butoxide, etc. are used to prepare a coating layer on the surface of the mixture. After the above coating materials are hydrolyzed, inorganic oxides such as silicon dioxide, aluminum oxide, and titanium dioxide can be coated on the surface of the mixture. On the one hand, the coating material acts as an adhesive to make the two materials combine more closely, which is beneficial to the energy transfer between the long afterglow phosphor and the perovskite quantum dots; on the other hand, as a coating, the stability of both and the fluorescence lifetime of the material are improved.

[0034] The preparation method of the wavelength-adjustable long afterglow composite material provided by the present invention comprises the following steps: S1, mixing the long afterglow fluorescent material with the perovskite quantum dot material to obtain a mixed powder, and dispersing it in an organic solvent; S2, dripping the coating material, hydrolyzing, drying, grinding, and sintering to obtain the wavelength-adjustable long afterglow composite material. The present invention utilizes the in-situ hydrolysis of the coating material to composite the perovskite quantum dot material with the long afterglow fluorescent material, and simultaneously completes the crystallization process of the perovskite quantum dots and the crystallization process of the coating material through the sintering step, thereby improving the stability of the composite material and avoiding the damage to the performance of the quantum dots caused by the composite process in the prior art after the crystallization of the quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 is a process flow chart of the preparation of the wavelength-adjustable long afterglow composite material in Example 1 of the present invention;

[0037] Figure 2 It is the comparison result of the wet heat aging of the materials provided in Example 1 of the present invention and Comparative Examples 1-2;

[0038] Figure 3 It is the UV aging comparison result of the materials provided in Example 1 of the present invention and Comparative Examples 1-2;

[0039] Figure 4 It is the high temperature aging comparison result of the materials provided in Example 1 of the present invention and Comparative Examples 1-2;

[0040] Figure 5 It is a comparison chart of the fluorescence lifetimes of the materials provided in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0041] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0043] Example 1

[0044] This embodiment provides a Lp-g-CsPbBrI2 red light long afterglow material, and its preparation process is as follows: Figure 1 As shown, the specific composition and preparation steps are as follows:

[0045] (1) First, accurately weigh each chemical substance according to the molar ratio of 30SiO2, 39B2O3, 5ZnO, 4Cs2CO3, 5CaO, 2PbO, 5KBr, and 10KI. After grinding, place the powder in a corundum crucible, and sinter it in a preheated muffle furnace at 1200°C for 10 minutes. After melting, pour the glass melt on a brass plate. After cooling, crush the glass and grind it to obtain powder A (perovskite quantum dot glass powder).

[0046] (2) Powder A is mixed with rare earth doped strontium aluminate phosphor SrAl2O4:Eu 2+ ,Dy 3+ (B powder, Dongguan Hongtai New Material Technology Co., Ltd. product number: 1206 blue-violet phosphor, the same below) was mixed and ball-milled at a mass ratio of 2:1 (450rpm, 4h), the ball-milled powder was passed through a 500-mesh sieve and dispersed in ethanol at 50ml / g, fully stirred in an open state, and the coating material tetraethyl orthosilicate was added dropwise, with the ratio of the coating material to A powder being 3mL / g. After fully stirring in an open state for 5h (complete hydrolysis), the ethanol was dried, and after grinding, it was sintered at medium temperature in an inert gas atmosphere (400℃ for 5h and then raised to 520℃ for 10h) to obtain a red light long afterglow material.

[0047] Example 2

[0048] This embodiment provides a Lp-g-CsPbBr3 green light long afterglow material, and its composition and specific preparation steps are as follows:

[0049] (1) First, accurately weigh each chemical substance according to the molar ratio of 30SiO2, 39B2O3, 5ZnO, 4Cs2CO3, 5CaO, 2PbO, and 12KBr. After grinding, place the powder in a corundum crucible, and sinter it in a preheated muffle furnace at 1200°C for 10 minutes. After melting, pour the glass melt on a brass plate. After cooling, crush the glass and grind it to obtain powder A (perovskite quantum dot glass powder).

[0050] (2) Powder A is mixed with rare earth doped strontium aluminate phosphor SrAl2O4:Eu 2+ ,Dy 3+ The mixed ball milling was carried out at a mass ratio of 2:1 (450rpm, 4h), and the powder after ball milling was dispersed in ethanol at 50ml / g through a 500 mesh sieve. The coating material tetraethyl orthosilicate was added dropwise with an open stirring, and the ratio of the coating material to the A powder was 3mL / g. After fully stirring for 5h, the ethanol was dried, and after grinding, the green light long afterglow material was obtained by medium temperature sintering in an inert gas atmosphere (400℃ for 5h and then raised to 480℃ for 6h).

[0051] Example 3

[0052] This embodiment provides a Lp-g-CsPbBr 1.5 Cl 1.5 The composition and specific preparation steps of the blue light long afterglow material are as follows:

[0053] (1) First, accurately weigh each chemical substance according to the molar ratio of 30SiO2, 39B2O3, 5ZnO, 4Cs2CO3, 5CaO, 2PbO, 6KBr, and 6KCl. After grinding, place the powder in a corundum crucible, and sinter it in a preheated muffle furnace at 1200°C for 10 minutes. After melting, pour the glass melt on a brass plate. After cooling, crush the glass and grind it to obtain powder A (perovskite quantum dot glass powder).

[0054] (2) Powder A is mixed with rare earth doped strontium aluminate phosphor SrAl2O4:Eu 2+ ,Dy 3+ The mixed ball milling was carried out at a mass ratio of 2:1 (450rpm, 4h), and the ball-milled powder was passed through a 500-mesh sieve and dispersed in ethanol at 50ml / g. The coating material tetraethyl orthosilicate was fully stirred in an open state and added dropwise. The ratio of the coating material to the A powder was 3mL / g. After fully stirring in an open state for 5h, the ethanol was dried, and after grinding, the medium-temperature sintering (380℃ for 5h and then raised to 450℃ for 6h) in an inert gas atmosphere was carried out to obtain a blue light long afterglow material.

[0055] Example 4

[0056] This embodiment provides a Lp-g-CsPbBr 1.5 I 1.5 The composition and specific preparation steps of the yellow light long afterglow material are as follows:

[0057] (1) First, accurately weigh each chemical substance according to the molar ratio of 30SiO2, 39B2O3, 5ZnO, 4Cs2CO3, 5CaO, 2PbO, 7KBr, and 7KI. After grinding, place the powder in a corundum crucible, and sinter it in a preheated muffle furnace at 1200°C for 10 minutes. After melting, pour the glass melt on a brass plate. After cooling, crush the glass and grind it to obtain powder A (perovskite quantum dot glass powder).

[0058] (2) Powder A is mixed with rare earth doped strontium aluminate phosphor SrAl2O4:Eu 2+ ,Dy 3+The mixed ball milling was carried out at a mass ratio of 2:1 (450rpm, 4h), and the powder after ball milling was dispersed in ethanol at 50ml / g through a 500 mesh sieve. The coating material tetraethyl orthosilicate was added dropwise in an open state with sufficient stirring. The ratio of the coating material to the A powder was 3mL / g. After sufficient stirring in an open state for 5h, the ethanol was dried, and after grinding, the medium temperature sintering (400℃ for 5h and then raised to 500℃ for 8h) in an inert gas atmosphere was carried out to obtain a yellow light long afterglow material.

[0059] Example 5

[0060] This embodiment provides a Lp-MS-CsPbBr3 green light long afterglow material, and its composition and specific preparation steps are as follows:

[0061] (1) PbBr2 and CsBr were weighed in a molar ratio of 1:1, and deionized water was added to dissolve by heating at 80°C with stirring. The mass ratio of water to solid was 1:100. After the solid was completely dissolved, MCM-41 molecular sieve was added, wherein the mass ratio of molecular sieve to PbBr2 was 3:1. The temperature was kept at 80°C and stirred slowly until the water was completely evaporated. The dried solid was ground through a 200-mesh sieve to obtain a precursor A powder.

[0062] (2) Powder A is mixed with rare earth doped strontium aluminate phosphor SrAl2O4:Eu 2+ ,Dy 3+ The mixed ball milling was carried out at a mass ratio of 2:1 (450rpm, 4h), and the powder after ball milling was dispersed in ethanol at 50ml / g through a 500 mesh sieve. The coating material tetraethyl orthosilicate was added dropwise in an open state with sufficient stirring. The ratio of the coating material to the A powder was 3mL / g. After sufficient stirring in an open state for 5h, the ethanol was dried, and after grinding, it was calcined at 700℃ in a muffle furnace for 30min, and cooled to room temperature to obtain the Lp-MS-CsPbBr3 green light long afterglow material.

[0063] Example 6

[0064] This embodiment provides a Lp-g-CsPbBrI2 red light long afterglow material. Compared with Embodiment 1, the only difference is that an equal volume of tetrabutyl titanate is used instead of tetraethyl orthosilicate.

[0065] Example 7

[0066] This embodiment provides a Lp-g-CsPb3 red light long afterglow material, which is different from Embodiment 1 only in that an equal volume of aluminum isopropoxide is used instead of tetraethyl orthosilicate.

[0067] Example 8

[0068] This embodiment provides a Lp-g-CsPbBrI2 red light long afterglow material. Compared with the embodiment 1, the only difference is that the same mass of rare earth doped calcium aluminate phosphor CaAl2O4:0.018Eu 2+ ,0.01Dy 3+ (Jinan Yuanpeng Chemical Co., Ltd.) replaces the long afterglow fluorescent material in Example 1.

[0069] Example 9

[0070] This embodiment provides a Lp-g-CsPbBrI2 red light long afterglow material. Compared with Embodiment 1, the only difference is that the mass ratio of A powder to B powder is 100:1.

[0071] Example 10

[0072] This embodiment provides a Lp-g-CsPbBrI2 red light long afterglow material. Compared with Embodiment 1, the only difference is that the mass ratio of A powder to B powder is 1:100.

[0073] Comparative Example 1

[0074] This comparative example provides a Lp-g-CsPbBrI2 red light long afterglow material, which is different from Example 1 only in that it does not include a coating layer, and the specific operation of step (2) is:

[0075] Powder A is mixed with the long afterglow fluorescent material SrAl2O4:Eu 2+ ,Dy 3+ The mixed powder is ball-milled at a mass ratio of 2:1 (450 rpm, 4 h), the ball-milled powder is sieved through a 500-mesh sieve, and sintered at medium temperature in an inert gas atmosphere (400°C for 5 h and then increased to 480°C for 6 h) to obtain a red light long afterglow material.

[0076] Comparative Example 2

[0077] This comparative example provides a Lp-g-CsPbBrI2 red light long afterglow material. Compared with Example 1, the only difference is that only hot injection method is used to prepare red light perovskite quantum dots CsPbBrI2 and long afterglow phosphor rare earth doped strontium aluminate phosphor SrAl2O4:Eu 2+ ,Dy 3+ Mix according to the mass ratio of 1:20.

[0078] Comparative Example 3

[0079] This comparative example provides a g-CsPbBrI2 material, which is different from Example 1 only in that no coating layer is included and no adhesive is added. The specific operation of step (2) is as follows:

[0080] Powder A was ball-milled (450 rpm, 4 h), the milled powder was passed through a 500-mesh sieve, and sintered at medium temperature in an inert gas atmosphere (400°C for 5 h and then raised to 480°C for 6 h) to obtain the product.

[0081] Test Case

[0082] The various properties of the embodiments and comparative examples were tested, and the specific testing methods were as follows:

[0083] Test method for the stability of composite materials: The composite material and the light-curing resin (D-5602 transparent UV glue of Foshan Jinggu Adhesive Co., Ltd.) were mixed evenly in a mass ratio of 1:20, degassed using a vacuum degassing machine, and then applied on a quartz glass sheet with a thickness of 150 microns. The test film was cured for 3 minutes using a 150w 365nm UV lamp.

[0084] Wet heat aging test: The test film is aged in a constant temperature and humidity chamber at a humidity of 95% and a temperature of 65°C.

[0085] UV aging test: Place the test film under a 150W, 365nm UV lamp at a distance of 25cm for aging.

[0086] 85℃ high temperature aging test: The test film is placed in a 85℃ forced air drying oven for constant temperature aging.

[0087] The test method of steady-state, transient spectra (fluorescence lifetime) and quantum yield is as follows: an Edinburgh FLS1000 steady-state transient fluorescence spectrometer with an integrating sphere accessory is used, and the excitation light wavelength is 365 nm.

[0088] The specific test results are shown in the table below:

[0089] Table 1

[0090] sample Emission peak Quantum yield Half peak width Fluorescence lifetime Example 1 640nm 74% 32nm 2.42h Example 2 518nm 75% 19nm 2.13h Example 3 454nm 39% 19nm 2.01h Example 4 593nm 62% 30nm 2.25h Example 5 642nm 69% 31nm 2.21h Example 6 638nm 76% 29nm 2.19h Example 7 639nm 78% 30nm 2.34h Example 8 637nm 76% 31nm 2.41h Example 9 639nm 73% 29nm 1.35h Example 10 639nm 75% 32nm 3.56h Comparative Example 1 639nm 79% 31nm 0.69h Comparative Example 2 637nm 85% 34nm 0.87h Comparative Example 3 637nm 85% 34nm 67ns

[0091] In order to compare the composite effect of the composite material, we compared the nanosecond fluorescence lifetime of the long afterglow phosphor (B powder in Example 1) itself and Example 1, Comparative Example 2, and Comparative Example 3. Figure 5 It can be seen that the decay curve of the long afterglow phosphor is nearly parallel to the x-axis, and the fluorescence intensity is stable, that is, stable long afterglow luminescence. Compared with comparative example 2, Example 1 is closer to the curve of the long afterglow phosphor, and the intensity is higher than that of comparative example 2. After a small amount of decay, the afterglow intensity tends to be stable, indicating that the composite effect of quantum dots and long afterglow phosphors in Example 1 is better, the fluorescence intensity of the afterglow is higher after leaving the excitation light source, and the energy transfer efficiency is high.

[0092] from Figure 2-4It can be seen that compared with the conventional binder (Comparative Example 2), the composite material provided by the embodiment of the present invention has significant advantages in terms of wet heat aging, UV aging and high temperature aging, indicating that it has higher stability. The composite material provided by the embodiment of the present invention is superior to the material without a coating layer (Comparative Example 1) in terms of wet heat aging, UV aging and high temperature aging. Although the difference is not particularly significant, the technical solution provided by the embodiment of the present invention has significant advantages in terms of fluorescence lifetime.

[0093] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A wavelength-adjustable long afterglow composite material, characterized in that: It includes a mixture of a long afterglow fluorescent material and a perovskite quantum dot material, and an inorganic oxide coating layer coated on the surface of the mixture; Wherein, the inorganic oxide coating layer is prepared from at least one of ethyl orthosilicate, tetramethyl orthosilicate, 3-aminopropyltriethoxysilane, tetrabutyl titanate, aluminum isopropoxide, and aluminum n-butoxide.

2. The wavelength-adjustable long afterglow composite material according to claim 1, characterized in that: The mass ratio of the long afterglow fluorescent material to the perovskite quantum dot material is 100:1-1:

100.

3. The wavelength-adjustable long afterglow composite material according to claim 1 or 2, characterized in that: The afterglow wavelength of the long afterglow fluorescent material can excite the perovskite quantum dot material.

4. The wavelength-adjustable long afterglow composite material according to claim 3, characterized in that: The long afterglow fluorescent material includes at least one of rare earth doped aluminate, rare earth doped silicate and sulfide fluorescent materials.

5. The wavelength-adjustable long afterglow composite material according to claim 3, characterized in that: The perovskite quantum dot material includes at least one of perovskite quantum dot glass, perovskite quantum dot@molecular sieve composite material, perovskite quantum dot@mesoporous material composite material, perovskite quantum dot@mesoporous material composite material, perovskite quantum dot@multi-level porous material composite material, and perovskite quantum dot core-shell coating material; And / or, the perovskite quantum dot material includes at least one of CsPbX3 and ion-doped perovskite quantum dots; Optionally, the composition of the ion-doped perovskite quantum dots is CsPb a M 1-a X3, M is selected from at least one of Sr, Ca, Ba, Mn and rare earth ions.

6. A method for preparing the wavelength-adjustable long afterglow composite material according to any one of claims 1 to 5, characterized in that: The steps include: S1, mixing a long afterglow fluorescent material with a perovskite quantum dot material to obtain a mixed powder, and dispersing the mixed powder in an organic solvent; S2, adding the coating material dropwise, hydrolyzing, drying, grinding, and sintering to obtain the wavelength-adjustable long afterglow composite material.

7. The method for preparing the wavelength-adjustable long afterglow composite material according to claim 6, characterized in that: In step S2, the sintering temperature is 200-700°C, and the sintering time is 30min-15h; Optionally, the sintering step includes maintaining the temperature at 380-420° C. for 2-6 hours, and then increasing the temperature to 450-540° C. for 3-10 hours; And / or, the sintering is performed under a protective atmosphere.

8. The method for preparing the wavelength-adjustable long afterglow composite material according to claim 6, characterized in that: The ratio of the amount of the coating material to the mixed powder is 0.2-20 mL / g.

9. The method for preparing the wavelength-adjustable long afterglow composite material according to any one of claims 6 to 8, characterized in that: In step S1, the ratio of the amount of the organic solvent to the mixed powder is 1-200 mL / g; And / or, the organic solvent comprises at least one of ethanol, propanol, n-hexane and cyclohexane; And / or, the particle size of the mixed powder is controlled to be 200-2000 mesh.

10. An application of the wavelength-tunable long afterglow composite material according to any one of claims 1 to 5 or the wavelength-tunable long afterglow composite material prepared by the preparation method according to any one of claims 6 to 9 in the fields of indicator lighting, architectural decoration, biological imaging, information storage, biological detection, anti-counterfeiting labels, photoelectric detectors or solar spectrum conversion.